EVALUATION OF BIOCHEMICAL POTENTIAL IN TOMATO (Solanum Lycopersicum L.) GERMPLASM FROM MEGHALAYA, INDIA - Uttam Paul1, Arindam Barman2 *, Prahash Chandra Sarma3and Neha M Sangma4 (Chelonian Research Foundation, 2023)
Eleven tomato genotypes were evaluated for physical and biochemical parameters collected from different regions of Meghalaya, India during 2019-2023. Results revealed based on physical parameters, that the maximum value recorded for dry matter was 10.33% whereas the lowest was 7.39%.The maximum value recorded for moisture content was 92.54%. The maximum value recorded for TSS was 23˚Brix. The samples were analyzed based on eight biochemical parameters. The highest value recorded for ascorbic acid, carbohydrates, non-reducing sugar, phenol, protein, reducing sugar and total sugar was61.84mg, 3.61%, 5.21%, 3.01mg, 7.78%, 3.41% and 4.52% respectively. The lycopene content recorded was 1.69mg per 100g of dry weight. Based on the experimental results it has been concluded that out of eleven samples, the red color cherry shaped tomatoes of average diameter 2.0 cm collected from Williamnagar (Sample No. 6) was found to have a good nutritional value because of its highest content of antioxidant lycopene. It was observed that the red color egg-shaped tomatoes of 4.4cm diameter of Resubelpara (Sample No. 3) was a good source of another antioxidant Ascorbic acid. It was recorded that the round-shaped sample of diameter 4.9 cm collected from Baghmara (Sample No. 5) having 87.02% moisture content was the lowest in quantityand hasalonger shelf life than the rest of the collected samples. Keywords: Tomato, Physical parameter, Biochemical parameter, Lycopene, Meghalaya